2010
DOI: 10.2527/jas.2009-2708
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding various quantities of wet and dry distillers grains to finishing steers on carcass characteristics, meat quality, retail-case life of ground beef, and fatty acid profile of longissimus muscle1

Abstract: Two hundred forty Angus crossbred steers were used to determine the influence of feeding various quantities of wet and dry distillers grains to finishing steers on carcass characteristics, meat quality, retail-case life of ground beef, and fatty acid profile of LM. Three replications of 5 dietary treatments were randomly applied to 15 pens in each of 2 yr. A finishing diet containing dry-rolled corn, soybean meal, and alfalfa hay was fed as the control diet. Wet distillers grains with solubles (DGS) or dry DGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 49 publications
4
43
1
Order By: Relevance
“…Hence, distillers grains are used widely in feedlot diets at levels varying from 10% to 80% on a DM basis. Although many beef quality studies (Roeber et al 2005;Koger et al 2010;Mello et al 2012) on feeding distillers grains reported no differences in tenderness between control and treatments, a recent study (Senaratne 2012) revealed an intriguing phenomenon. Beef from steers fed 30% wet distillers grains plus solubles (WDGS) was more tender than beef from steers not fed WDGS, and this is not the first time that feeding distillers grains is reported to improve tenderness (Depenbusch et al 2009;Segers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, distillers grains are used widely in feedlot diets at levels varying from 10% to 80% on a DM basis. Although many beef quality studies (Roeber et al 2005;Koger et al 2010;Mello et al 2012) on feeding distillers grains reported no differences in tenderness between control and treatments, a recent study (Senaratne 2012) revealed an intriguing phenomenon. Beef from steers fed 30% wet distillers grains plus solubles (WDGS) was more tender than beef from steers not fed WDGS, and this is not the first time that feeding distillers grains is reported to improve tenderness (Depenbusch et al 2009;Segers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of differing inclusion rates of DGS on aspects such as shelf life and tenderness of beef products have been evaluated (Depenbusch et al, 2009;Kroger et al, 2010), few reports on the effect of the S concentration of the diet on meat quality are available.…”
Section: Effects On Carcass and Meat Characteristicsmentioning
confidence: 99%
“…In a research by Koger et al [2010], the control group was receiving soybean meal in feed rations whereas the experimental groups were administered wet or dried distillers grains. A higher content of C17:0 acid and lower contents of C18:0, C18:1t, C16:1c9, and C 18:2 c9c12 acids and of the total PUFA were noted in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, due to a high content of protein, the DDGS may be applied in fatteners feeding as a substitute for high-protein feeds, e.g. soybean or rapeseed meal [Robinson et al,, 2008;Koger et al, 2010;Łozicki et al, 2010;Szulc et al, 2010]. They may be administered directly to feed rations or used as a raw material in the production of concentrates.…”
Section: Introductionmentioning
confidence: 99%